Clinical Evaluation of the Articulinx Intercarpometacarpal Cushion for the First CMC Joint: A Feasibility Study - van der Veen, Fiente J. C.; White, David N.; Dapper, Mattie M. L.; Griot, J. Peter W. don; Ritt, Marco P. J. F. (Journal of Wrist Surgery, 2013)
Background The Intercarpometacarpal Cushion (ICMC; Articulinx, Cupertino, CA, USA) is an implantable spacer designed as a less invasive surgical treatment for osteoarthritis (OA) of the first carpometacarpal joint (CMC-1).Description of Technique Following local anesthesia and exposure of the joint capsule the ICMC, attached to a needle and suture tethers, is guided into the joint space under fluoroscopic visualization through a dorsal approach. The needle is pulled through the thenar eminence to the opposite side of the hand and, once proper device placement is confirmed, cut free and the joint capsule closed.Patients and Methods Eight female patients (median age 56 years; range, 42–83) were treated and followed for 6 to 24 months. Safety of the implant procedure was evaluated intraoperatively. Pain, joint function, and strength were evaluated at 6 weeks, 3, 6, 12 and 24 months with a Visual Analog Scale (VAS) for pain, the QuickDASH inventory, Canadian Occupational Performance Measure (COPM), and pinch and grip strength measurements.Results At 2 years (n = 6), mean VAS pain scores decreased from 6.3 (± 1.5) to 2.2 (± 1.1) (p < 0.001), mean QuickDASH scores improved from 47 (± 15) to 31 (± 11) (p < 0.10), mean COPM performance scores improved from 5.0 (± 1.2) to 5.5 ( ± 1.3) (p = NS). Mean pinch and grip strength measurements also improved compared with baseline. No serious adverse events occurred. Two device removals occurred, associated with a traumatic event and Stage IV OA with device displacement, at 6 and 9 months respectively.Conclusion The ICMC can be implanted safely. Effectiveness needs to be confirmed in future studies.
Keywords: carpometacarpal; osteoarthritis; spacer; arthroplasty; intercarpometacarpal cushion